Simple Bouquet Homemade: Creative Business Innovation for Economic Enrichment of the Community in the Blora Randublatung Cursed Village - Munir, Akhmad Sirojudin; Luthfi Hidayah; Suci Yongki Setiowati; Nurul Mustafidah (PT. ALHAFI BERKAH INDONESIA, 2024)
The program